Designing a Citizenship Rights Curriculum Model for the Second Period of Elementary Education - Kafshchian Moghadam, Ansieh; Maleki, Hasan; Sadeghi, Alireza (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study aimed to design a curriculum model for citizenship rights for students in the second period of elementary education. It sought to examine the components of the citizenship rights curriculum, introduce the main components and categories forming this field, and ultimately provide an ideal model in line with needs assessment and educational context. Methodology: The methodology of this study was qualitative, utilizing a grounded theory approach. The collection and formulation of model categories involved 21 structured interviews with experts and teachers in the field of citizenship and civil rights education, followed by the validation of the proposed model using a member checking method. Findings: The findings of this research presented a model comprising 11 main categories including causal conditions, performance-based planning, contextual conditions, contextually oriented performance-based planning (political, economic, cultural, legal, and citizenship orientations), interveners (characteristics of teachers and learners), strategies (initial, educational, and feedback), and outcomes (enhancing student performance levels and creating a sustainable curriculum). Conclusion: Specialized multi-faceted planning was identified as the core category of the model. Finally, recommendations were provided.